[tex]\displaystyle \left \{ {{5u+4v=11} \atop {u+6v=-3}} \right. \\\\\left \{ {{5u+4v=11} \atop {u=-3-6v}} \right.\\ \\5(-3-6v)=4v=11\\v=-1\\u=-3-6(-1)\\u=3\\(u,v)=(3,-1)[/tex]
[tex]\begin{cases}5u+4v=11\\u+6v=-3\quad|\cdot(-5)\end{cases}= > \ \ +\begin{cases}5u+4v=11\\-5u-30v=15\end{cases} \begin{array}{lcl}= > -26v=26\\= > \ \ v=-1\end{array}[/tex]
[tex]u=-3-6v=-3-6(-1)=-3+6=3[/tex]
ответ: (u; v) = (3; -1)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\displaystyle \left \{ {{5u+4v=11} \atop {u+6v=-3}} \right. \\\\\left \{ {{5u+4v=11} \atop {u=-3-6v}} \right.\\ \\5(-3-6v)=4v=11\\v=-1\\u=-3-6(-1)\\u=3\\(u,v)=(3,-1)[/tex]
[tex]\begin{cases}5u+4v=11\\u+6v=-3\quad|\cdot(-5)\end{cases}= > \ \ +\begin{cases}5u+4v=11\\-5u-30v=15\end{cases} \begin{array}{lcl}= > -26v=26\\= > \ \ v=-1\end{array}[/tex]
[tex]u=-3-6v=-3-6(-1)=-3+6=3[/tex]
ответ: (u; v) = (3; -1)